New procedure for electronic deliveries in administrative proceedings (Ius Novum, 2023)
The subject of this study is related to the new procedure of electronic deliveries in administrative jurisdictional proceedings regulated by the provisions of the Code of Administrative Procedure. The main research objective was not only to describe de lege lata the modes of individual deliveries with the indication of their mutual hierarchy, but also several issues related to the mutual relationship between the Code and the Act on electronic deliveries. Both normative acts require co-existence, and thus the determination of which of them, in which situational variants, will be qualified as lex generali. This task is by no means facilitated by the fact that the characteristics of the framework regulation can be found in the code, while the Act “model” regulates the rules of communication with the participation of public entities. The main thesis presented in the study is the need for systemic interpretation of the provisions of the latter. The author is also of the opinion that the definition of the scope of exclusions from the application of the Act was not designed correctly. The issues raised have not been the subject of articles so far.
Keywords: electronic delivery; informatization of administration; public law; electronic communication; administration